Find all positive integers x , y and positive prime numbers p such that
p x − y p = 1 .
Enter your answer as the sum ∑ ( p i + x i + y i ) , where the sum runs over the solutions ( p , x , y ) to the equation.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice usage of Mihailescu's theorem, though that is considerably a high power theorem.
Hmm, Mihailescu's theorem makes this a bit too easy. I had intended it to be an application of the LTE lemma , applied to p x = y p + 1 .
Log in to reply
[hide= "solution "] X =$V p(y^p+1)$ =$v p(y+1)+v_p(P)$ It forces to solution
Case p = 2 : If x > 1 then 2 x ≡ 0 m o d 4 and since y is odd, its square is then ≡ 1 m o d 4 , so the difference is 0 − 1 ≡ − 1 ≡ m o d 4 but on the RHS we have ≡ 1 m o d 4 , hence whenever p = 2 we have x ≤ 1 , by trial and error one finds the only solution: x = 1 , y = 1 , p = 2
Case p > 2 : If p ∣ y then y = k ⋅ p and hence p x − ( k p ) p = 1 is never reached. (consider modulo p ), so p ∣ y and the LTE conditions are satisfied. Then we write the original equation as y p + 1 p = p x and obtain:
v p ( y p + 1 p ) = v p ( p x ) ⟺ v p ( p ) + v p ( y + 1 ) = x ⟺ v p ( y + 1 ) = x − 1
We then use the inequality; p v p ( y + 1 ) ≤ y + 1 to get
p ( x − 1 ) ≤ y + 1 ⟺ p x ≤ ( y + 1 ) p
Finally we arrive at the following inequality;
p(y+1)-y^p\ge 1\tag 1
We now use Fermat's little theorem;
y p ≡ y m o d p and y p + 1 = p x gives that p ∣ ( y + 1 ) and since p > 2 this yields y ≥ 2 and then ( 1 ) cannot hold for large p (this is left to you), namely only for x = 2 , y = 2 , p = 3
Problem Loading...
Note Loading...
Set Loading...
Note that p > 1 because it's a prime number. We divide into two cases.
Case 1 : x > 1
Since x , p > 1 , this means p x , y p are perfect powers. By Mihăilescu's theorem , the only pair of perfect powers that differ by 1 is 2 3 = 8 and 3 2 = 9 . This gives ( p , x , y ) = ( 3 , 2 , 2 ) .
Case 2 : x = 1
Then p = y p + 1 . If p is odd, then y p + 1 factorizes to ( y + 1 ) ( y p − 1 − y p − 2 + … − y + 1 ) , which means y p + 1 is not prime. Thus p must be even, giving p = 2 . This leads to y = 1 , so the solution is ( p , x , y ) = ( 2 , 1 , 1 ) .
Thus the only two solutions are ( p , x , y ) = ( 2 , 1 , 1 ) , ( 3 , 2 , 2 ) , giving sum of 11.